SUNFLOWER PLANT RESPONSE TO SIMULATED DRIFT OF GLYPHOSATE AND TRINEXAPAC-ETHYL - VITAL,R.G. (2017)
ABSTRACT Chemical ripeners are frequently used on sugarcane crops in order to increase profitability. However, the drift of these products to neighbouring fields can expose susceptible non-target plants, such as sunflower, to these agents causing indirect impacts on growth and development. Therefore, this study aimed to assess the toxicity characterize possible changes in the growth of sunflower plants exposed to simulated drift of the ripeners glyphosate and trinexapac-ethyl. For each ripener, the following doses were used: glyphosate (0 (control), 3.6, 7.2, 14.4, 28.8 and 86.4 g a.e ha-1) and trinexapac-ethyl (0, 3.12, 6.25, 12.50, 25 and 75 g a.i ha-1). The effects of these products on plant height, number of leaves, leaf area, stem diameter and dry matter (leaves, stem, flower, root, shoot and total) were evaluated. We also conducted a visual analysis of symptoms of phytotoxicity after exposure. The effects of the ripeners on sunflower plants varied depending on the type of agent used and the dose. Plants treated with glyphosate showed altered growth patterns, indicating high sensitivity of these plants to the herbicide. With increasing doses, glyphosate drift promoted lower growth and development of sunflower plants and negatively affected productivity. Nevertheless, trinexapac-ethyl drift, in the evaluated doses, did not affect sunflower plants.